2016
DOI: 10.1016/s0959-8049(16)61456-9
|View full text |Cite
|
Sign up to set email alerts
|

Gli1/DNA interaction is a druggable target for Hedgehog-dependent tumors

Abstract: Hedgehog signaling is essential for tissue development and stemness, and its deregulation has been observed in many tumors. Aberrant activation of Hedgehog signaling is the result of genetic mutations of pathway components or other Smo-dependent or independent mechanisms, all triggering the downstream effector Gli1. For this reason, understanding the poorly elucidated mechanism of Gli1-mediated transcription allows to identify novel molecules blocking the pathway at a downstream level, representing a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 44 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…This relieves the repressive activity on Smoothened (SMO), resulting in its accumulation and activation of the GLI1 transcription factor [17]. The GLI1 protein contains five successive DNA-binding zinc finger motifs, of which the first three bind the phosphate backbone, while the last two bind target DNA in a sequence-specific way [18]. The C-terminal region has a transactivation function through modulation of chromatin remodelling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relieves the repressive activity on Smoothened (SMO), resulting in its accumulation and activation of the GLI1 transcription factor [17]. The GLI1 protein contains five successive DNA-binding zinc finger motifs, of which the first three bind the phosphate backbone, while the last two bind target DNA in a sequence-specific way [18]. The C-terminal region has a transactivation function through modulation of chromatin remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…(D) Plexiform fibromyxoma with GLI1 polysomy (case 15), showing immunopositivity for GLI1 in the vast majority of tumour cells. (E, F) Tumours without evident GLI1 involvement demonstrate either insubstantial positivity (case 2) or lack immunopositivity for GLI1 (case 13) High protein levels of GLI1 can be the result of amplification of the GLI1 gene, epigenetically driven overexpression, mutations in the SUFU or PTCH1 genes or post-synthetic modifications [18,21]. Likewise, activation of the Hedgehog signalling pathway may be possible by low-level gains of the 12q13 region containing the GLI1 gene in two plexiform fibromyxomas of our tumour cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, functional experiments using gain-or loss-of-function studies demonstrated that the FOXM1/IPO7/GLI1 axis promotes GBM cell proliferation, migration, and invasion. A well known characteristic of GLI1 is that it is often overexpressed in human glioma cells (30,31), and it directly regulates expression of oncoproteins, including cyclin D1/D2 (32), FOXM1 (13), and epithelialto-mesenchymal transition-related proteins (33), and thus promotes the proliferation and invasion of tumor cells. We found that FOXM1 expression correlated directly with GLI1 expression in human GBM specimens, further confirming that these two important transcriptional factors have potential clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs directly bind to and antagonize GLI transcription factors by interfering with their processing, ciliary trafficking, or DNA binding. GANT58, GANT61, and Glabrescione B (GLaB) are thought to inhibit the transcriptional output of Hh signaling by interfering with GLI DNA-binding [130][131][132], whereas HPIs exert their activity through several mechanisms including inhibition of GLI processing (HPI 1), impaired conversion of GLI to GLI A (HPI 2,3) and disruption of ciliary processes required for GLI function (HPI 4) [133]. Drug repurposing strategies have also identified ATO as a potent selective GLI inhibitor with two proposed mechanisms of actions: direct inhibition of the transcriptional activity of GLI1 or interference with ciliary trafficking (early effect) and enhanced degradation of GLI2 (delayed effect) [134,135].…”
Section: Direct Gli Inhibitorsmentioning
confidence: 99%